2018
DOI: 10.1016/j.celrep.2018.08.010
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Visual Cues, Reward, and Motor Feedback on the Representation of Behaviorally Relevant Spatial Locations in Primary Visual Cortex

Abstract: SummaryThe integration of visual stimuli and motor feedback is critical for successful visually guided navigation. These signals have been shown to shape neuronal activity in the primary visual cortex (V1), in an experience-dependent manner. Here, we examined whether visual, reward, and self-motion-related inputs are integrated in order to encode behaviorally relevant locations in V1 neurons. Using a behavioral task in a virtual environment, we monitored layer 2/3 neuronal activity as mice learned to locate a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 31 publications
2
63
1
Order By: Relevance
“…At first, all regions of the corridor generated equal amounts of neural activity in the visual cortex. But once the 'reward zone' had gained significance, most of the visual cortical neurons started to fire only there 10 .…”
Section: Impossible Worldsmentioning
confidence: 99%
“…At first, all regions of the corridor generated equal amounts of neural activity in the visual cortex. But once the 'reward zone' had gained significance, most of the visual cortical neurons started to fire only there 10 .…”
Section: Impossible Worldsmentioning
confidence: 99%
“…Our results show that in a familiar environment, V1 is influenced by the physical distance run: when the distance is increased or decreased, V1 neurons respond at a position that is intermediate between the actual position where visual cues are displayed and the physical distance at which the animal used to encounter these visual cues. A possibly similar effect was seen in V1 neurons selective to a rewarded position; their firing may depend on the physical distance run, at least when no salient visual cue is present (Pakan et al, 2018). Here, we showed that this integration of visual cues and distance information in V1 may also happen throughout the trajectory of the animal in the corridor: in our dataset, V1 neurons exhibited a shift in their response when the distance changed, whether they fired preferentially at the reward position or elsewhere.…”
Section: Figure 4 Spatial Representations In V1 and Ca1 Depend On Thementioning
confidence: 58%
“…There is increasing evidence that the responses of neurons in primary visual cortex (V1) are influenced by the animal's position in the environment (Fiser et al, 2016;Haggerty and Ji, 2015;Ji and Wilson, 2007;Pakan et al, 2018;Saleem et al, 2018). Positions encoded by V1 neurons match those encoded by regions of the navigational system such as the hippocampus (Haggerty and Ji, 2015;Saleem et al, 2018) and fluctuations in the spatial position encoded by the V1 population correlate with those observed in hippocampus CA1 (Saleem et al, 2018).…”
mentioning
confidence: 99%
“…Inputs from the anterior cingulate cortex have been attributed to modulate locomotor signals (Fiser et al, 2016;Leinweber et al, 2017), and those from the claustrum could be involved in change detection and modulating the salience of visual cues (Brown et al, 2017;Atlan et al, 2018). Spatial signals modulating V1 activity (Pakan et al, 2018;Saleem et al, 2018;Fournier et al, 2019) could be routed through areas detected that are also known to have spatial signals, including the retrosplenial cortex (Witter et al, 2017;Mao et al, 2018;Nitzan et al, 2020) , or the entorhinal and subicular areas (Witter et al, 2017).…”
Section: Diverse Areas Projecting To the Primary Visual Cortexmentioning
confidence: 99%
“…Neural activity in the mouse primary visual cortex (V1) is known to be modulated by a variety of contextual signals, including arousal, locomotion, spatial context, spatial attention, or navigation (Niell and Stryker, 2010;Keller et al, 2012;Saleem et al, 2013Saleem et al, , 2018McGinley et al, 2015;Poort et al, 2015;Vinck et al, 2015;Fiser et al, 2016;Jurjut et al, 2017;Pakan et al, 2018;Speed et al, 2020). Perturbations of specific areas have been found to alter some contextual modulations in V1, including mesencephalic locomotor region (MLR) and effects of locomotion (Lee et al, 2014), or anterior cingulate cortex (ACC) and effects of sensorimotor prediction (Leinweber et al, 2017).…”
Section: Introductionmentioning
confidence: 99%